Mass Spectrometry of Membrane Proteins: A Focus on Aquaporins - Schey, Kevin L. (Biochemistry, 2013)
[Image: see text] Membrane proteins are abundant, critically important biomolecules that conduct essential functions in all cells and are the targets of a significant number of therapeutic drugs. However, the analysis of their expression, modification, protein–protein interactions, and structure by mass spectrometry has lagged behind similar studies of soluble proteins. Here we review the limitations to analysis of integral membrane and membrane-associated proteins and highlight advances in sample preparation and mass spectrometry methods that have led to the successful analysis of this protein class. Advances in the analysis of membrane protein posttranslational modification, protein–protein interaction, protein structure, and tissue distributions by imaging mass spectrometry are discussed. Furthermore, we focus our discussion on the application of mass spectrometry for the analysis of aquaporins as a prototypical integral membrane protein and how advances in analytical methods have revealed new biological insights into the structure and function of this family of proteins.